The operas of Mozart - Greenberg, Robert, 1954-; Teaching Company (Chantilly, Va. : Teaching Co., 2002)
Discusses Mozart's most important operas.
lecture 17. Mozart, Masonry and the Magic flute -- lecture 18. Magic flute, part two -- lecture 19. Magic flute, part three -- lecture 20. Magic flute, part four -- lecture 21. Magic flute, part five -- lecture 22. Magic flute, part six -- lecture 23. Magic flute, part seven -- lecture 24. Magic flute, part eight.
DVD, region 1.
Lecturer: Robert Greenberg.
Course Number 780: 24 lectures (45 minutes/lecture).
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791 -- Criticism and interpretation; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Mozart, Wolfgang Amadeus, -- 1756-1791.; Operas -- Analysis, appreciation